KESIMPULAN UMUM, DAFTAR PRESENSI, DENAH LOKASI, INDEX KATA KUNCI, INDEX AUTHOR - SEMBIO XII (Universitas Sebelas Maret, 2015)
KESIMPULAN UMUM, DAFTAR PRESENSI, DENAH LOKASI, INDEX KATA KUNCI, INDEX AUTHOR